Rodzina a pomyślność gospodarcza państwa - Hypś, Sławomir (Przegląd Prawno-Ekonomiczny, 2008)
Streszczenie dostępne wyłącznie w języku angielskim: The stage of development of civilization of 21st century demands a new attitude to the question of economic processes going on in the world. The type of economy hitherto existing and concentrated upon the biggest possible profit seems to be an inadequate solution as it has led to a specific social crisis most clearly visible in the highly developed countries. That is why it is necessary to draw new objects of modern economy based on the common welfare of all people, the essence, objective and guiding principle of which is man and his good. It must be the economy of new humanism, i.e it’s central point is to be man and his good in the aspect of community. The new humanism should specially be seen in the care for family. Family is a community of people, which is the basis of everybody’s existence. The close relationship of a man with his/her family has also substantial influence upon the economic situation of the state which is “a family of families”. Such formulation of the objectives of economy, in the face of crisis of earlier conceptions, is viewed upon with a growing interest. Nowadays the economic liberals, who are adverse to any interference of the state in the economic processes, appeal to the government to promote active pro – family politics. The civilization development during the latest centuries resulting from the appearance of new possibilities and new people’s needs and necessity to provide for tchem caused great socio – economic changes. The results of those changes, connected mainly with two economic processes, i.e. industrialization and urbanization are still present in the life of the society and they are characterized nowadays mainly by the proceeding division of labour, migration, mechanization, and automatization of the process of labour and production, discovering new materials and more effective sources of energy, growth of productivity, and the resulting growth of the national revenue, as well as the origin and development of big cities and city – industrial agglomerations. Those changes are not meaningless for the institution of family, which experiences a crisis due to them – it is revealed in a more and more frequent disturbances of its natural structure and functions. A family that does not perform it tasks immediately weakens the state which is a form of social organization. Thus we may formulate a thesis about the existence of close relationship between the situation of the state – also the economic situation – and the condition of a family - its economic is in a specific way a requisite of the economic development of the country. The prosperity of families is thus the basis of prosperity of the state.